2021
DOI: 10.1155/2021/5555590
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Hypoxia-Induced Senescence of Human Bone Marrow Mesenchymal Stem Cells

Abstract: Background and Aim. The senescence of human bone marrow mesenchymal stem cells (hBMSCs) can be induced by oxidative stress, but the mechanism by which it occurs is not yet clear. Here, we performed an investigation on the pathogenesis of hypoxia-induced senescence through proteomic analyses and aimed to explore the mechanisms of stem cell senescence. Methods. Hypoxia in hBMSCs was induced for 0, 4, and 12 hours, and cellular senescence was evaluated by senescence-associated β-galactosidase (SA-β-gal) staining.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…Liquid chromatographytandem mass spectrometry analysis was performed using a Q Exactive hybrid quadrupole orbitrap mass spectrometer (Thermo Scientific, Waltham, MA, USA). The raw data for each sample were searched using the MASCOT engine (version 2.2; Matrix Science, London, UK) embedded in Proteome Discoverer 1.4 software (Thermo Scientific, Waltham, MA, USA) for identification and quantitation analysis [57][58][59]. The proteomics data have been deposited to the ProteomeXchange Consortium via the iProX partner repository with accession number PXD040406.…”
Section: Transcriptomic and Proteomic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid chromatographytandem mass spectrometry analysis was performed using a Q Exactive hybrid quadrupole orbitrap mass spectrometer (Thermo Scientific, Waltham, MA, USA). The raw data for each sample were searched using the MASCOT engine (version 2.2; Matrix Science, London, UK) embedded in Proteome Discoverer 1.4 software (Thermo Scientific, Waltham, MA, USA) for identification and quantitation analysis [57][58][59]. The proteomics data have been deposited to the ProteomeXchange Consortium via the iProX partner repository with accession number PXD040406.…”
Section: Transcriptomic and Proteomic Analysesmentioning
confidence: 99%
“…To analyze differences in protein expression among groups, a fold change of >1.2 or <0.83 and a p-value of <0.05 were used to identify up and downregulated proteins. NCBI Basic Local Search Tool (BLAST) + client software (NCBI-blast-2.2.28+-win32.exe, Bethesda, Maryland, USA) and InterProScan were used to find homolog sequences for the selected DEPs [58,60]. The GO, Pfam, KEGG, Non-Redundant, and Swiss-Prot databases were used to annotate all sequences using a BLAST search (http://blast.ncbi.nlm.nih.gov/Blast.cgi) (accessed on 1 November 2022) [56,61].…”
Section: Protein Identification and Bioinformatic Analysismentioning
confidence: 99%
“…The key differential proteins that were screened for involvement in ferroptosis processes are HMOX1, TFR1, SLC3A2 and NCOA4. These target proteins were further validated via parallel reaction monitoring (PRM) [26][27][28][29][30], the roles of HMOX1, TFR1 and SLC3A in ferroptosis were successfully validated via PRM, and the overall trend of PRM validation results and TMT experimental results were in high agreement, which supported the proteomics data rationality and reliability. Therefore, the identified differentially expressed proteins became the focus of further research into disease resistance mechanisms.…”
Section: Discussionmentioning
confidence: 58%
“…Proteomics identified Cox7c to be involved in oxidative phosphorylation and metabolism pathways. Cox7c, a member of the cytochrome c oxidase complex responsible for mitochondrial respiration promotes ATP synthesis and reduces mitochondrial dysfunction [ 59 ]. Recent studies have revealed Cox7c to be a potential biomarker of pathogenesis in Alzheimer's disease [ 60 ].…”
Section: Discussionmentioning
confidence: 99%